2013
DOI: 10.1002/jcc.23505
|View full text |Cite
|
Sign up to set email alerts
|

Why is N···Be distance of NH3H+···DBeH shorter than that of NH3D+···HBeH? paradoxical geometrical isotope effects for partially isotope‐substituted dihydrogen‐bonded isotopomers

Abstract: The partial isotope substitution for the change of geometrical parameters, interaction energies, and nuclear magnetic shielding tensors (σ) of dihydrogen-bonded NH3X(+)···YBeH (X, Y = H, D, and T) systems is analyzed. Based on the theoretical calculation, the distance between heavy atoms RN···Be of NH3H(+) ···DBeH is clearly found to be shorter than that in NH3D(+)···HBeH. Such apparently paradoxical geometrical isotope effect (GIE) on RN···Be is revealed by the cooperative effect of two kinds of (1) primary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 26 publications
(15 reference statements)
0
20
0
Order By: Relevance
“…For quantitative discussion, nuclear orbital should be expanded by a suitable number of nuclear basis functions, and electron–nucleus and nucleus–nucleus correlation effects should be evaluated. However, we have already demonstrated that H/D isotope effect can be adequately analyzed by MC_MO‐MP2 calculations, in which only electron–electron correlation effect is taken account and only single s ‐type GTF is adopted as the nuclear basis function . We first performed the geometry optimization of the systems with the conventional MP2/6‐311G** level of calculation and confirmed that the optimized geometries correspond to stable structures by vibrational harmonic frequency calculations.…”
Section: Methodsmentioning
confidence: 71%
See 2 more Smart Citations
“…For quantitative discussion, nuclear orbital should be expanded by a suitable number of nuclear basis functions, and electron–nucleus and nucleus–nucleus correlation effects should be evaluated. However, we have already demonstrated that H/D isotope effect can be adequately analyzed by MC_MO‐MP2 calculations, in which only electron–electron correlation effect is taken account and only single s ‐type GTF is adopted as the nuclear basis function . We first performed the geometry optimization of the systems with the conventional MP2/6‐311G** level of calculation and confirmed that the optimized geometries correspond to stable structures by vibrational harmonic frequency calculations.…”
Section: Methodsmentioning
confidence: 71%
“…Consequently, our methods can conveniently reproduce the H/D GIEs, since electronic wavefunction obtained in multicomponent calculations directly reflects the difference of nuclear quantum nature of light nuclei. We have successfully revealed the H/D isotope effects on geometries, interaction energies, rate constants, and various properties in several HB systems with the aid of MC_MO and MC_DFT methods …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the accuracy of MCMO calculations, we have to evaluate not only electron–electron correlation effect but also electron–nucleus and nucleus–nucleus correlation effects, since light nuclei are also treated quantum‐mechanically. We, however, considered only electron‐electron correlation effect in MCMO‐MP2 and MC‐DFT calculations in this study, because we already demonstrated that the H/D isotope effect on energies and geometries could be adequately evaluated without including electron–nucleus and nucleus‐nucleus correlation effects . We used the 6‐31G, 6‐31G*, 6‐31G**, 6‐31 + G**, 6‐31++G**, 6‐311G, 6‐311G**, and 6‐311++G** electronic basis sets to analyze the effect of the size of the electronic basis set on the distribution of nuclear wavefunction, and we adopt a single s ‐type GTF for the nuclear basis function.…”
Section: Methodsmentioning
confidence: 99%
“…In the MCMO method, the concept of MOs for electrons is extended to the nuclear case and light nuclei are treated as quantum wavefunction as well as electrons under the fixed classical nuclei. The difference between nuclear quantum natures of isotopomers is directly reflected in the electronic states, and consequently our MCMO method can describe the H/D isotope effect on geometries (geometrical isotope effect: GIE) conveniently . Several groups also have developed their own multicomponent methods and successfully analyzed interesting chemical and physical phenomena .…”
Section: Introductionmentioning
confidence: 99%